Juridical implications of election of the general election of the Regional Council of Representatives (DPD) with the Noken System - Waluyo,; Nurjaya, I Nyoman; Suryokumoro, Herman; Hadiyantina, Shinta (Technium Social Sciences Journal, 2021)
In addition to the general election that applies nationally, there are general elections held by indigenous peoples with the noken or ikat system in Papua Province, especially in the central highlands of Papua. The election with the noken system began to be recognized by the general public when the Constitutional Court of the Republic of Indonesia through Decision Number 47-81 / PHPU.A-VII / 2009 on General Election Result Disputes (PHPU) in Yahukimo Regency, recognized the noken system as a legitimate means of election . Elections with the noken system are simply seen as a system of using noken bags as a substitute for ballot boxes in the implementation of the General Election. There are juridical implications in the context of regulation (legal validity) related to the election of DPD members who are elected using the Noken system. Many Constitutional Court decisions have not been followed up by the DPR in the form of laws, for example the Constitutional Court Decisions Number 47-81 / PHPU.A-VII / 2009. If examined more deeply, the legitimacy in this Constitutional Court decision is not placed in the verdict, but is placed in consideration (considering). This shows that the legitimacy of using the noken system is still weak due to the incomplete legal norms according to Stuffenbau Theorie. At the technical level, this decision was only followed up by the Papua Provincial KPU through Decree Number 01 / Kpts / KPU Prov. 030/2013 concerning Technical Instructions for Voting Procedures Using Noken as a Substitute for Ballot Boxes, and the Indonesian KPU through Decree No. 810 / PL. 02.6-Kpt / 06 / KPU / IV / 2019 concerning Guidelines for Voting Using the Noken / Ikat System in Papua in the 2019 Election.